HOW DOES THE RELIGION INFLUENCE THE EMPLOYEE ENGAGEMENT IN INDONESIAN CONTEXT? - Febriansyah, Hary (Jurnal Manajemen Bisnis, 2019)
The implementation of religion in the workplace exists; however, it needs more techniques to be explored and discussed. Therefore, this study was challenged and conducted in an emerging country which has very diverse on religion and cultures combining with a high diversity of companies and its level. This study used a qualitative method with interviews to examine the influence of religious factors on employee engagement in the context of the Indonesian companies. The findings indicate that employees feel more engaged when there is freedom to express religious faith in the workplace, besides the traditional human resources management system elements.